Measurement of Tourism Sensitive Compactness Level in Kasongan Tourism Area - Dwi Aryo Nugroho; Muhammad Sani Roychansyah (Department of Architecture and Planning, Faculty of Engineering, Universitas Gadjah Mada, 2021)
Yogyakarta province is currently experiencing an increase in population growth, urbanization and the economy resulting in an increase in the community's need space for work and living space . But not supported by the availability of workspace and occupancy coupled with high land prices. the high vehicle population increases every year reduces the comfort level of the city result in people triggered to choose workspaces and residences in the suburbs of Yogyakarta. Kasongan is tourism area located in Bangunjiwo Village, Bantul Regency, located in the suburbs of Yogyakarta, being choice of the community. However, this can trigger urban sprawl because there is'n good regional planning. Jenks Compact City is solution to overcome the phenomenon of Urban Sprawl. this reseach aims to determine the level of compactness Kasongan area. The study was conducted by conducting field observations and interviews to be able to identify land uses, activities within the area, affordability of public facilities, and distribution of public transportation. The results of observations found that the building density is low, affordability of public facilities is not ideal, there are no transit points or regional public transportation.